INVESTIGATIONS OF THE VITAMIN E IMPACT ON ERYTHROCYTE MEMBRANES' STATE IN MERCURY POISONING (Eurasian Journal of Ecology, 2025)
Mercury is considered as one of the most dangerous substances found on the Earth surface. Various sources can release mercury into the air, waterways and soils,which is chemically transforms result in further toxic effects on the environment and human health. The negative effects of mercury depend primarily on the type of mercury, because different forms of mercury have different levels of bioavailability, bioaccumulation, and toxicokinetics. The toxic effects of mercury compounds include abdominal pain, nausea, vomiting, blood toxicity, kidney, lung, digestive and nervous system damage, memory disorders, fatigue, muscle weakness, skin and eye irritation, toxic effects on the reproductive system, impaired immune system. In biological pathways, mercury undergoes both oxidation and reduction reactions, leading to changes in its appearance and affecting its biological uptake. The molecular mechanism of toxicity caused by inorganic mercury compounds includes disruption of cell membranes, disruption of cell integrity and permeability, inhibition of enzymes involved in antioxidant defense mechanisms, and promotion of oxidative damage. In this regard, it is important to find effective ways to prevent and treat mercury intoxication and its harmful effects on the body. This article presents the results of a study of the state of erythrocyte membranes during acute and chronic mercury intoxication, as well as the possibility of increasing the resistance of membranes with the help of vitamin E. The research results obtained indicate the effectiveness of the use of vitamin E in order to achieve an antioxidant effect that prevents damage and destruction of erythrocyte membranes, as for acute and chronic mercury intoxication.Keywords: erythrocyte membrane, mercury, intoxication, hemolysis, vitamin E, resistance